Konferenser - Haglund, Bo J.A. (Socialmedicinsk tidskrift, 2018)
10th IUHPE European Conference and International Forum for Health Promotion Research Implementing Health Promotion in the Life Course - User Involvement in Practice and Research 24-26 September 2018 in Trondheim, Norway 11th European Public Health Conference 28 nov - 1 dec 2018 Cankarjev dom, Ljubljana, Slovenia